2017
DOI: 10.5414/cn109034
|View full text |Cite
|
Sign up to set email alerts
|

Does Helicobacter pylori infection play a role in iron deficiency anemia in hemodialysis patients?

Abstract: H. pylori infection has a nonsignificant effect on iron deficiency anemia in hemodialysis patients. We recommend that routine screening for H. pylori is not needed among dialysis patients with iron deficiency anemia.
.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…Many studies did not find a significant relationship between anemia and iron deficiency with HP positivity and other endoscopic findings except bleeding [61]. We detected significant relationship between duedonitis and lower hemoglobin.…”
Section: Discussioncontrasting
confidence: 37%
“…Many studies did not find a significant relationship between anemia and iron deficiency with HP positivity and other endoscopic findings except bleeding [61]. We detected significant relationship between duedonitis and lower hemoglobin.…”
Section: Discussioncontrasting
confidence: 37%
“… 20 Even so, an Egyptian study conducted with 90 chronic kidney disease patients on hemodialysis also found no significant differences between H. pylori -positive and -negative groups for any of the variables analyzed including hemoglobin, serum iron, ferritin and transferrin saturation. 21 In addition, an Egyptian study conducted in 60 children found that the soluble transferrin receptor in serum was significantly higher in the H. pylori -positive group compared to the H. pylori -negative group although no significant differences were noted in hematologic variables and iron parameters between the two groups. 22 This variability in studies could be due to differences in the geographical and ethnical distribution of patients, age, inclusion criteria, sample size, sampling procedures, methods of detecting anemia, and methods of detecting H. pylori infection.…”
Section: Discussionmentioning
confidence: 98%
“…Cardenas VM et all., (2012), выдвинул предположение, что НР оказывает подавляющий эффект на дуоденальную СО, которые непосредственно ответственны за поглощение железа [39]. Но данным El-Said H. et al, (2017), не имеется существенные различия между показателями железодефицитной анемии у HР-положительными/НР-отрицательными пациентами: гемоглобин (8,96 ± 1,8 против 9,76 ± 1,4 g/dL), сывороточное железо (86 ± 17,5 против 87 ± 18,2 pg/dL), ферритин (284,8 ± 60,5 против 301,4 ± 50,1 ng/dL) или индекс насыщение трансферрина -TSAT (26,79 ± 18,42% против 29,83 ± 18,01% μg/dL) [40].…”
Section: связь между железодефицитной анемией и хеликобактериозомunclassified